Ectopic vortex veins and varices in Donnai Barrow syndrome. (4th March 2022) - Higham, Aisling; Hildebrand, Göran Darius; Graham-Evans, Katharine A. J.; Gilbert, Rodney D.; Horton, Rachel; Hunt, David; Shears, Deborah; Patel, Chetan Kantibhai
ABSTRACT: Background: Donnai Barrow Syndrome (DBS) is a rare, multi-system autosomal recessively inherited disorder of relevance to ophthalmologists. To aim to describe the ocular phenotype using multimodal imaging for two cases of genetically confirmed DBS and compare against the published phenotype. Materials and methods: Retrospective case series of two unrelated patients with DBS and review of the literature. Both cases were referred to our tertiary unit for laser prophylaxis against retinal detachment. Results: There was extreme high myopia greater than 20 dioptres without rhegmatogenous retinal detachment (RRD). Anterior segment features included iris transillumination and ciliary body hypoplasia. Posterior segment changes included previously described changes of optic nerve hypoplasia and a strikingly abnormal appearance of the fundus consisting of multiple bilateral giant posterior vortex veins (PVV). The mouse model shows a similar phenotype. Conclusions: Ectopic vortex veins of the choroid expand the phenotype of DBS and can be helpful in distinguishing the differential diagnosis of high myopia in children. Posterior vortex veins have been described in adult high myopia as acquired but our cases suggest that they could be congenital. Orbital manipulation and hypotony during surgery should be avoided to minimise complications. The evidence to recommend prophylactic laser retinopexy in these cases is inconclusive, and overall we recommend that conservative management should be considered using wide-angle retinal imaging in the clinic.